Remote patient's health monitoring / Mohd Azhar Mohd Razali - Mohd Razali, Mohd Azhar (Faculty of Information Technology and Quantitative Sciences, 2005)
As the Internet begins to play a greater role in many healthcare processes, it is inevitable that remote monitoring of patients' physiological parameters over the Internet will become increasingly commonplace. Internet-based commimication between patients and their healthcare providers has aheady become prevalent, and has gained significant attention in terms of confidentiality issues. Continuous monitoring of physiological signals has the potential to greatly improve the quaUty of life of patients with diseases. Recent advances in sensor technology make the capture of such signals possible. In this paper, we present Remote Patient's Health Monitoring, a real-time, operator-based system solution for managing physiological patient's body temperate reading.. The system processes data using the device simulator that acts as real time body temperature sensor. The architecture is scalable, allowing implementation on systems ranging fi'om desktops to server farms. It guarantees real-time response and data persistence in a distributed environment. We apply this prototype system to the problem that arises with current medical system.